Efficient and Selective Removal of Heavy Metals and Dyes from Aqueous Solutions Using Guipi Residue-Based Hydrogel - Xiaochun Yin; Pei Xu; Huiyao Wang (Gels, 2024)
The presence of organic dyes and heavy metal ions in water sources poses a significant threat to human health and the ecosystem. In this study, hydrogel adsorbents for water pollution remediation were synthesized using Guipi residue (GP), a cellulose material from Chinese herbal medicine, and chitosan (CTS) through radical polymerization with acrylamide (AM) and acrylic acid (AA). The characteristics of the hydrogels were analyzed from a physicochemical perspective, and their ability to adsorb was tested using model pollutants such as Pb2+, Cd2+, Rhodamine B (RhB), and methyl orange (MO). The outcomes revealed that GP/CTS/AA-co-AM, which has improved mechanical attributes, effectively eliminated these pollutants. At a pH of 4.0, a contact duration of 120 min, and an initial concentration of 600 mg/L for Pb2+ and 500 mg/L for Cd2+, the highest adsorption capabilities were 314.6 mg/g for Pb2+ and 289.1 mg/g for Cd2+. Regarding the dyes, the GP/CTS/AA-co-AM hydrogel displayed adsorption capacities of 106.4 mg/g for RhB and 94.8 mg/g for MO, maintaining a stable adsorption capacity at different pHs. Compared with other competitive pollutants, GP/CTS/AA-co-AM demonstrated a higher absorption capability, mainly targeted toward Pb2+. The adsorption processes for the pollutants conformed to pseudo-second-order kinetics models and adhered to the Langmuir models. Even after undergoing five consecutive adsorption and desorption cycles, the adsorption capacities for heavy metals and dyes remained above 70% and 80%. In summary, this study effectively suggested the potential of the innovative GP/CTS/AA-co-AM hydrogel as a practical and feasible approach for eliminating heavy metals and dyes from water solutions.